2020
DOI: 10.3389/fcell.2020.588476
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress- and Drug-Induced Histone Modifications Within the Ventral Tegmental Area

Abstract: Psychiatric illnesses are a major public health concern due to their prevalence and heterogeneity of symptom presentation resulting from a lack of efficacious treatments. Although dysregulated dopamine (DA) signaling has been observed in a myriad of psychiatric conditions, different pathophysiological mechanisms have been implicated which impede the development of adequate treatments that work across all patient populations. The ventral tegmental area (VTA), a major source of DA neurons in the brain reward pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 119 publications
0
10
0
Order By: Relevance
“…Direct comparison of rodent and human reward circuitry development in the neonatal periods is lacking, although it is suggested that rodent brain development is shifted relative to human development such that the first week of rodent life is approximately aligns with the last trimester of human gestation ( 16 , 88 ). While a majority of rodent models of ELS begin ELS in the first few days after birth ( 86 , 89 ), some shift stress to start around P9-10 ( 82 , 90 , 91 ). Each of these models of ELS have been documented to alter pups' plasma corticosterone levels acutely ( 85 , 92 , 93 ), although the long-term impact on basal and stress-induced corticosterone appear to depend on type and timing of stress (reviewed in ( 86 ).…”
Section: Impact Of Early Life Stress On Motivated Behavior and Reward Circuit Activity From Non-human Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct comparison of rodent and human reward circuitry development in the neonatal periods is lacking, although it is suggested that rodent brain development is shifted relative to human development such that the first week of rodent life is approximately aligns with the last trimester of human gestation ( 16 , 88 ). While a majority of rodent models of ELS begin ELS in the first few days after birth ( 86 , 89 ), some shift stress to start around P9-10 ( 82 , 90 , 91 ). Each of these models of ELS have been documented to alter pups' plasma corticosterone levels acutely ( 85 , 92 , 93 ), although the long-term impact on basal and stress-induced corticosterone appear to depend on type and timing of stress (reviewed in ( 86 ).…”
Section: Impact Of Early Life Stress On Motivated Behavior and Reward Circuit Activity From Non-human Animal Modelsmentioning
confidence: 99%
“…Post-translational modifications to histone protein tails – including acetylation, methylation, and other modifications – can increase or decrease compaction, and repress or allow gene expression, respectively. 24-h maternal deprivation at P9 ELS has been shown to alter histone acetylation in VTA, which is directly linked to altered GABAergic function in VTA and increased dopaminergic excitability, and which is restored by histone deacetylase inhibitor treatment ( 90 , 91 , 141 , 177 ). ELS (combined maternal separation and limited nesting material from P10-17) also broadly altered levels of post-translational histone modifications in NAc across postnatal development in a sex-specific manner ( 178 ).…”
Section: Impact Of Early Life Stress On Transcription and Epigenetic Regulation Within Nacmentioning
confidence: 99%
“…Increasing evidence has confirmed that at least 12 types of specific modifications occur to the N-terminal amino acid residues of histones, which affect the nucleosomes bind to DNA and the three-dimensional structure of chromosomes, and regulate gene expression. The patterns of histone modification are the following way: acetylation (lysine), methylation (lysine and arginine), phosphorylation (serine and threonine), sumoylation (lysine), ubiquitylation (lysine), ADP ribosylation, butyrylation, citrullination, crotonylation, formylation, proline isomerization, propionylation, serotonylation, and dopaminylation (glutamine) [ 4 , 5 ]. The nomenclature of histone modification is as follows, such as H3K9me3, H3 refers to the core histone protein, K refers to the amino acid, the number 9 indicates the position of lysine residue from the N-terminal end of the amino acid tail of histone protein, and me3 refers to the type of modification on the lysine residue [ 6 ].…”
Section: Histone Modificationmentioning
confidence: 99%
“…Sensitivity to reward is modulated by prior experiences, particularly during early developmental periods [1][2][3][4][5][6][7][8][9][10][11]. In the United States, over 30% of children experience some type of early-life adversity (ELA) related to poverty, trauma, and chaotic environments [12] and these events have been associated with poor cognitive and emotional health [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%